Comparing Ultrasonography and Endoscopy for Early Gender Identification of Juvenile Siberian Sturgeon. (1st November 2013) - Munhofen, Jennifer L.; Jiménez, David A.; Peterson, Doug L.; Camus, Alvin C.; Divers, Stephen J.
Abstract: Early gender identification is economically advantageous in sturgeon aquaculture to facilitate the targeting of food and spatial resources to females for caviar production. In addition, many species of free‐ranging sturgeon are threatened or critically endangered, and the ability to identify gender and evaluate gonads can reveal pertinent biological information that can lead to better management and recovery plans. We compared the speed and accuracy of ultrasonography and endoscopy in identifying gender in 143 juvenile Siberian Sturgeon Acipenser baeri using gonadal histology as the gold standard. The age‐3 and age‐4 sturgeon were anesthetized with buffered tricaine methanesulfonate and evaluated using ultrasonography and endoscopy; endoscopic gonadal biopsy was then done for histologic confirmation. All fish recovered normally, and there was no postprocedural morbidity or mortality. Histology confirmed the gender for 128 of the 140 (91.4%) fish. Histology and endoscopy agreed on the gender of 124 of the 128 (96.9%) fish, while histology and ultrasonography agreed on 113 of the 128 (88.3%) fish. Ultrasonography (mean time, 11.2 s) was significantly faster than endoscopy (22.3 s), while endoscopy was more accurate but more invasive. Diagnostic accuracy, speed, and invasiveness are factors to consider when selecting a method of gender identification for commercial and free‐ranging populations.